Impact of Climate Change on Health and Livelihoods of Pastoral Communities in Kenya: A Case of North Eastern Region - Wanjara, Amos Otieno; Ogembo, Paul O (CV. Literasi Indonesia, 2023)
The geospatial locale of the North Eastern Region naturally experiences dryness which when coupled with climate change poses a big threat to the livelihood and health of the communities therein. The region has of late experienced prolonged drought with serious ramifications on the health of the surrounding communities together with their livestock. The purpose of this paper is to assess the effect of climate change on the livelihoods and health of the Pastoral communities in N.E Kenya. The objectives of the study were: to establish how climate change affects the livelihoods of the pastoral communities; to establish the effect of climate change on the health of the pastoral communities in Kenya and to establish the appropriate intervention measures that could be put in place to address the climate change issues with its ramifications on the pastoralists in Kenya. The findings show that climate change has negative impacts on the health and socio-economic livelihoods of the pastoralists. The study used an empirical literature review adopting a meta-analytical approach. The study has implications on the policy directions on how to deal with the impacts of climate change on pastoralists, towards helping them adapt to the situation with resilience, while ensuring their welfare is guaranteed.